Additional use of an aldosterone antagonist in patients with mild to moderate chronic heart failure: a systematic review and meta‐analysis. (8th April 2013) - Hu, Li‐jun; Chen, Yun‐qing; Deng, Song‐bai; Du, Jian‐lin; She, Qiang
<x xml:space="preserve">Abstract</x> Aims Aldosterone antagonists (AldoAs) have been used to treat severe chronic heart failure (CHF).There is uncertainty regarding the efficacy of using AldoAs in mild to moderate CHF with New York Heart Association (NYHA) classifications of I to II. This study summarizes the evidence for the efficacy of spironolactone (SP), eplerenone (EP) and canrenone in mild to moderate CHF patients. Methods PubMed, MEDLINE, EMBASE and OVID databases were searched before June 2012 for randomized and quasi‐randomized controlled trials assessing AldoA treatment in CHF patients with NYHA classes I to II. Data concerning the study's design, patients' characteristics and outcomes were extracted. Risk ratio (RR) and weighted mean differences (WMD) or standardized mean difference were calculated using either fixed or random effects models. Results Eight trials involving 3929 CHF patients were included. AldoAs were superior to the control in all cause mortality (RR 0.79, 95% CI 0.66, 0.95) and in re‐hospitalization for cardiac causes (RR 0.62, 95% CI 0.52, 0.74), the left ventricular ejection fraction was improved by AldoA treatment (WMD 2.94%, P = 0.52). Moreover, AldoA therapy decreased the left ventricular end‐diastolic volume (WMD −14.04 ml, P < 0.00001), the left ventricular end‐systolic volume (WMD −14.09 ml, P < 0.00001). A stratified analysis showed a statistical superiority in the benefits of SP over EP in reducing LVEDV and LVESV. AldoAs reduced B‐type natriuretic peptide concentrations (WMD −37.76 pg ml−1, P < 0.00001), increased serum creatinine (WMD 8.69 μmol l−1, P = 0.0003) and occurrence of hyperkalaemia (RR 1.78, 95% CI 1.43, 2.23). Conclusions Additional use of AldoAs in CHF patients may decrease mortality and re‐hospitalization for cardiac reasons, improve cardiac function and simultaneously ameliorate LV reverse remodelling.